"Am iz kwiin" (I'm his queen): Combining interpretative phenomenological analysis with a feminist approach to work with gems in a resource-constrained setting. Issue 2 (3rd April 2019) - Clifford, Gayle; Craig, Gill; McCourt, Christine
ABSTRACT: This article focuses on working with gems using a feminist approach to interpretative phenomenological analysis (IPA) in a resource-constrained setting. The research explores the experiences of maternal disclosure of HIV to children of HIV positive mothers in Kingston, Jamaica. A feminist approach helps recognise power imbalances within research relationships and the women's lived experiences. We present three "gems" which illuminate women's lived experiences and explore how popularised representations of women's sexuality and mothering influence disclosure discourses. We use emotion work as a conceptual resource to structure the women's narratives and challenge existing policy discourses, which arguably represent disclosure within a binary, rationalist, decision-making framework. This article adds to global literature on maternal HIV disclosure and problematises policy discourses by bringing into relief the emotion work women engage in when deciding if and how to communicate their HIV status to their children. It adds to the body of research using IPA, particularly in resource-constrained settings where IPA has thus far had little application.